Using contemporary compositional techniques in teaching improvisation to children - Lasko, Agnieszka (Kansas State University, 2024)
This lecture-recital investigates the inclusion of improvisation within the framework of beginning and intermediate piano students. It includes simplified versions of improvisational techniques known from the works of composers of the 20th and 21st centuries. Elements of improvisation based on clearly defined rules help guide the spontaneous activities of beginners and provide new ideas. To ensure the comfort of both teachers and students, a balance was maintained between structure and creative elements. Consequently, work on the pieces begins with following the score first and then improvising. Additionally, all the pieces were written with a certain musical or technical point in mind to support the development of piano skills at the early stage of their piano education.
Keywords: Piano beginners; Piano pedagogy; Improvisation